Captivate the science of succeeding with people - Edwards, Vanessa van. (New York Portfolio, 2018)
As a human behavior hacker, Vanessa Van Edwards created a research lab to study the hidden forces that drive us. And she?s cracked the code. In Captivate, she shares shortcuts, systems, and secrets for taking charge of your interactions at work, at home, and in any social situation. These aren?t the people skills you learned in school. This is the first comprehensive, science backed, real life manual on how to captivate anyone?and a completely new approach to building connections.
Keywords: Social interaction